Numerical solution for the chemotaxis model by finite difference method - Messikh, Chahrazed; Chowdhury, Md. Sazzad Hossien; Guesmia, Amar; Mawa, Shukranul; Okhunov, Abdurahim; Mt Aznam, Suazlan (Institute of Physics Publishing, 2020)
The finite difference method for discretization space fractional chemotaxis model is introduced in this study. The space fractional chemotaxis system is obtained from the classical advection-diffusion equations of the chemotaxis system by replacing the spatial derivative with a generalized derivative of fractional order. We compare the numerical solution of finite difference method and exact solution for a test example. The results reveal that the finite difference method is very simple and efficient for solving space fractional chemotaxis system.